Answer:
Equation of tangent:
![y = xe^(x)](https://img.qammunity.org/2021/formulas/mathematics/college/ssq60iftc5y6ox77p4x9ck4w51mtgizjdr.png)
At point (1,0):
y = 2.713
Explanation:
The equation of tangent line to the function can be calculated by taking the first derivative.
We have,
![y = xe^(x)-e^(x)\\(dy)/(dx)=(d)/(dx)[ xe^(x) ]-(d)/(dx) [e^(x)]\\](https://img.qammunity.org/2021/formulas/mathematics/college/lpyge9rjhccgemp8n8adb6g3bazm305buj.png)
Applying Product Rule:
d/dx [u.v] = (d/dx u) . (v) + (u) . (d/dx v)
Therefore,
![(dy)/(dx)=(d)/(dx)(x) . e^(x)+x .(d)/(dx)(e^(x))- (d)/(dx)(e^(x))\\\\(dy)/(dx)=(1)(e^(x))+(x)(e^(x))-e^(x)\\ (dy)/(dx)=xe^(x)\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/kofk71efw57d5oylq8xvgbkl5ysu57yg6v.png)
The above equation is the equation of tangent line.
The point given is (1,0):
So,
![(dy)/(dx) = (1)e^(1)\\ (dy)/(dx) = e\\(dy)/(dx) = 2.713](https://img.qammunity.org/2021/formulas/mathematics/college/wx1wipy8ug2da58vkxd4vpmojv1yxl4ddf.png)